The Impact of COVID-19 Pandemic on the (Un)popularity of Higher Tourism Education in Poland - Mateusz Rozmiarek; Ewa Malchrowicz-Mośko (Kazimierz Wielki University, 2022)
Along with the development of tourism activities, universities educating students in the fields of tourism and recreation take over the responsibility for preparing a qualified and skilled workforce that can provide the society with high-quality services. The aim of the article was to attempt to assess the impact of the COVID-19 pandemic on the popularity or unpopularity of tourist faculties at Polish physical education universities. Five out of six public universities of physical education in Poland, which offer undergraduate and graduate studies in tourism and recreation were asked to provide data on the number of students who enrolled in the first and second cycle studies in the field of tourism and recreation in the last six years, as well as the number of students who resigned during the first year or after its completion. The results showed a decline in interest in studying tourism and recreation after the 2016/2017 academic year, which covers all physical education universities in Poland. Although there may be many reasons for this, it is necessary to try to find a solution to the current problems and restore interest in studying tourism.